2021
DOI: 10.1002/ajpa.24300
|View full text |Cite
|
Sign up to set email alerts
|

First direct evidence of conservative foraging ecology of early Gigantopithecus blacki (~2 Ma) in Guangxi, southern China

Abstract: Objectives Gigantopithecus blacki, the largest hominoid known, is one of the representative Pleistocene mammals in southern China and northern Southeast Asia. Here we investigate the feeding ecology of G. blacki in its core habitat (Guangxi, Southern China) during the early Early Pleistocene, which was the early period in its evolution. Materials and methods The stable isotopic (C, O) analysis of tooth enamel of the fauna associated with G. blacki (n = 58), including the largest number of G. blacki teeth (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…Data from published studies with a similar scope and objective were used as reference (Table SI 3) 12,17,[25][26][27][28][29][30][31][32][33][34][35][36][37] . These studies also analysed the carbonate fraction of dental enamel.…”
Section: Methodsmentioning
confidence: 99%
“…Data from published studies with a similar scope and objective were used as reference (Table SI 3) 12,17,[25][26][27][28][29][30][31][32][33][34][35][36][37] . These studies also analysed the carbonate fraction of dental enamel.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon (C) and oxygen (O) isotopic analyses of tooth enamel have suggested that G. blacki foraged in densely forested habitat and consumed C3 plants exclusively (Zhao et al, 2011;Zhao and Zhang, 2013;Nelson, 2014;Qu et al, 2014;Bocherens et al, 2017;Jiang et al, 2021). In this paleoecological context, potential food sources would have been plentiful, leading to speculation about the foods possibly consumed by G. blacki, such as fruits (Woo, 1962;Ciochon et al, 1990;Han and Zhao, 2002;Wang, 2009), tough items (Daegling and Grine, 1994;Zhao and Zhang, 2013), and/or hard objects (Ciochon et al, 1990;Kupczik and Dean, 2008;Qu, 2014;Hu et al, 2022).…”
Section: Potential Future Directions To Gain Insights Into the Dietar...mentioning
confidence: 99%
“…Attempts have been made to determine the dietary behavior of G. blacki through a variety of approaches, such as dentognathic morphology (e.g. enamel thickness, tooth root length, occlusal area, and mandibular corpus depth; Woo, 1962;Olejniczak et al, 2008a;Kupczik and Dean, 2008;Zhang and Zhao, 2013;Kono et al, 2014;Zhang and Harrison, 2017), stable isotope analysis (Nelson, 2014;Qu et al, 2014;Bocherens et al, 2017;Jiang et al, 2021;Hu et al, 2022), dental microwear (Daegling and Grine, 1994;Zhao and Zhang, 2013), incidence of dental caries (Han and Zhao, 2002;Wang, 2009), analysis of phytoliths (Ciochon et al, 1990), and analysis of starch grains (Qu, 2014). These studies provided indications-e.g.…”
Section: Introductionmentioning
confidence: 99%